The Relation between D-Dimer, Hs-CRP, and ACE Inhibitor to Severity, Reinfection, and Mortality of COVID-19 Patients - Thomas, Novita Silvana; Aphridasari, Jatu; Setijadi, Ana Rima (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: COVID-19 reinfection has been found, although the data is not clear yet. Pandemic conditions bring about limited facilities and infrastructure, so biomarkers are an option. Research on biomarkers and the use of ACE inhibitor drugs in COVID-19 patients has not been widely conducted in Indonesia.Methods: This was a retrospective cohort study that used medical record data of confirmed COVID-19 patients treated at dr. Moewardi General Hospital for the period of January to March 2022. Surviving patients were observed for reinfections until November 2022.Results: This study involved 524 medical records of confirmed COVID-19 patients. After exclusion and inclusion criteria, 517 medical records were obtained. D-Dimer cut-off values of ≥2435 were significantly related to severity (OR=2.05; 95% CI=1.38-3.06; P≤0.001) and mortality (OR=2.89; 95% CI=1.95-4.27; P≤0.001) of COVID-19 patients. Hs-CRP levels ≥4.59 were significantly associated with mortality in COVID-19 patients (OR=1.82; 95% CI=1.23-2.69; P=0.003). The use of ACE inhibitors (OR=0.55; 95% CI=0.33-0.89; P=0.015) was a protective factor from mortality but increased the risk of reinfection (OR=3.11; 95% CI=1.16-8.36; P=0.034). Conclusion: D-Dimer and Hs-CRP biomarkers could be considered as predictor biomarkers for the severity and mortality of COVID-19 patients. Although the use of ACE inhibitors increased the risk of reinfection, it reduced the risk of mortality due to COVID-19.